(untitled) (Research, Society and Development, 2021)
Textile industry uses dyes in the dyeing processes, generating effluents with potential toxicity to the environment and humans, if not treated adequately. Biosorption is an alternative for removing dyes from aqueous matrices, being a low-cost and effective technique, also allowing the use of agroindustrial wastes. Therefore, this work aimed to evaluate the capacity to remove the direct scarlet red dye using cassava bagasse as a biosorbent, a waste widely generated in Brazil. The biosorbent was characterized according to its specific surface area. Initially, preliminary tests were performed to obtain the best conditions of pH, temperature, and speed of rotation. Kinetic and adsorption equilibrium tests were performed. Mathematical modeling was employed in order to understand the mechanisms involved in the adsorption of the dye. The cassava bagasse had a specific surface area of ​​3.012 m² g-1, with the presence of micropores. The batch biosorption tests obtained optimal operating conditions at pH 2, 50 °C and 90 rpm. In kinetics, removal of 84% was achieved in 300 min. In adsorption isotherms, the maximum monolayer adsorption capacity estimated by the Langmuir model was 25.1 mg g-1. In mathematical modeling, both Pseudo-first order, Pseudo-second order and Elovich models represent kinetic data, suggesting the occurrence of more than one mechanism in the process, whereas, in isotherms, the Redlich-Peterson and Toth models suggest a trend to the Freundlich model. In general, cassava bagasse proved to be an efficient adsorbent in removing the textile dye.